Thermo-mechanical analysis of bolted X20 steam pipe-flange assembly. (2021) - Salifu, Smith; Desai, Dawood; Fameso, Festus; Ogunbiyi, Olugbenga; Jeje, Samson; Rominiyi, Azeez
Abstract: Flanges are vital component used in power generation plants for linking, closing and connecting of pipes to the boiler and turbine compartments. The linking of piping networks via this approach has limited the use of welding in the industry. High temperature, pressure and thermal transitions are presumed to influence the behaviour of bolted flange assemblies in service. Sadly, the behaviour of bolted steam pipe-flange assembly under these conditions have not been sufficiently studied. Thus, the usage, maintenance and replacement of the steam pipe flanges are based on assumptions which can have detrimental consequences. In order to investigate this under-researched area, the thermo-mechanical behaviour of a bolted X20 (12Cr-1MoVNi) steam pipe-flange assembly subjected to a typical power generation plant operational condition was determined using finite element analysis code, Abaqus CAE/2019. The stress and strain distribution across the assembly were computed and the maximum stress in the assembly was developed on the low temperature, high compressive stress side of the bolt's shank while the maximum strain was developed on the interior surface of the pipe. Also, the value of the maximum stress (331.8 MPa) developed on the bolts is below the operational limiting stress of the assembly material, thus, indicating that the assembly is operating within the acceptable stress, but with the bolts being identified as the component most prone to failure.